(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The risks associated with computer systems have been enormous for many years and still exist today. This article discusses several types of risks, including security, privacy, and judicial risks. Risk is usually defined as a function of event likelihood and impact and is divided into two categories speculative and non-speculative. Speculative risk is the risk of taking risks to gain potential benefits. There are two main ways to assess risk quantitative and qualitative. Risk management means consciously determining risk exposure. The starting point for the risk management process is to determine the risk acceptance criteria and reflect the risks that people are willing to accept.